2023
DOI: 10.1093/ageing/afac308
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic and corresponding control measures on long-term care facilities: a systematic review and meta-analysis

Abstract: Background Long-term care facilities (LTCFs) were high-risk settings for COVID-19 outbreaks. Objective To assess the impacts of the COVID-19 pandemic on LTCFs, including rates of infection, hospitalisation, case fatality, and mortality, and to determine the association between control measures and SARS-CoV-2 infection rates in residents and staff. Method We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…5,6 Similarly, COVID had a major impact on SNF and other long-term care facilities that adopted efforts to reduce disease spread within their facilities such as limiting access and admissions. 7 Second, the 3-day hospitalization rule primarily applied, and thus the waiver had the most potential impact, on fee-for-service (FFS) beneficiaries of Medicare. Other alternative Medicare coverage, such as most Medical Advantage plans and Accountable Care Organizations may not have had the 3-day requirement under their agreements with CMS during the study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Similarly, COVID had a major impact on SNF and other long-term care facilities that adopted efforts to reduce disease spread within their facilities such as limiting access and admissions. 7 Second, the 3-day hospitalization rule primarily applied, and thus the waiver had the most potential impact, on fee-for-service (FFS) beneficiaries of Medicare. Other alternative Medicare coverage, such as most Medical Advantage plans and Accountable Care Organizations may not have had the 3-day requirement under their agreements with CMS during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…For example, during the initial months following the declaration of the public health emergency, ED census across the nation fell markedly, including in California 5,6 . Similarly, COVID had a major impact on SNF and other long‐term care facilities that adopted efforts to reduce disease spread within their facilities such as limiting access and admissions 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need to better understand the indirect impact of COVID-19 on care-home residents, families and friends, and staff. For example, control measures which had some effect in reducing the risk of transmission [ 47 ] are recognised to have adverse effects on individuals and relationships [ 48–50 ]. Research is needed to understand the balance of benefits and harms of different control measures [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 1-day study in 9 geriatric hospitals in France and Switzerland in December 1987, totalling 1,919 patients, 44% aged more than 85 years and 74% being female, found a high rate of infections (18.7% in males and 15.4% in females) [8]. In a systematic review of 108 studies, Zhang showed a SARS-CoV-2 infection rate of 32.63% for residents [9]. In a prospective, longitudinal study, Aronow et al [10] investigated the major clinical cause of death among all residents aged 60 years older in a large nursing home.…”
Section: Burden Of Infectious Respiratory Diseases In Long-term Care ...mentioning
confidence: 99%